2012
DOI: 10.4067/s0718-95162012005000010
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical characteristics and nutrient uptake and distribution associated with the Cd-phytoremediation capacity of Eucalyptus camaldulenses Dehnh

Abstract: Cadmium (Cd) is a hazardous heavy metal whose concentrations have been increasing in Brazilian soils, largely due to mining activities. Eucalyptus species are widely planted in Brazil to produce raw materials, and the confirmation of their phytoremediation potential would link their economic and environmental roles. We examined the Cd-tolerance of Eucaliptus camaldulenses Dehnh and the anatomical and physiological features associated with that capacity. Plants were grown under greenhouse conditions in nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
7
17
0
Order By: Relevance
“…In fact, in plant-based water decontamination systems the root biomass can be totally harvested, thus removing the absorbed metal. The accumulation of Cd in the roots of eucalypt plants is in agreement with findings by Gomes et al (2012) and Fine et al (2013).…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 80%
See 2 more Smart Citations
“…In fact, in plant-based water decontamination systems the root biomass can be totally harvested, thus removing the absorbed metal. The accumulation of Cd in the roots of eucalypt plants is in agreement with findings by Gomes et al (2012) and Fine et al (2013).…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 80%
“…6). Consistent with the limited literature present on the matter (Gomes et al 2012, Fine et al 2013), the two clones showed a low capability to translocate Cd in the aerial parts, and no differences were observed between the clones with respect to this physiological process.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 76%
See 1 more Smart Citation
“…In plants, cadmium (Cd) exposure affects several morphological and physiological processes, altering water balance, nitrogen metabolic activities, and nutrient uptake and distribution (Dal Corso et al, 2010;Diwan et al, 2010;Gomes et al, 2012). Cadmium can also interact with photosynthesis by competing for root absorption with other metals (i.e., Mg, Fe, Mn, Zn) that are important cofactors of enzymes, pigments and structural components of the photosynthetic apparatus, reducing metabolic capacity for CO 2 fixation (Pietrini et al, 2010a;Basa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to Gomes et al (2012), dry weight (DW) production was negatively affected by Cd concentrations. Cd had inhibiting effects on growth up to concentrations of 45 µmol Cd; at higher concentrations, dry biomass production of both shoots and roots showed only slight changes.…”
Section: Figure 2 Root Length (A) and Root Weight (B) Of Remediator mentioning
confidence: 99%